2012
DOI: 10.1103/physrevlett.109.193602
|View full text |Cite
|
Sign up to set email alerts
|

Photon Blockade in the Ultrastrong Coupling Regime

Abstract: We explore photon coincidence counting statistics in the ultrastrong coupling regime, where the atom-cavity coupling rate becomes comparable to the cavity resonance frequency. In this regime, usual normal order correlation functions fail to describe the output photon statistics. By expressing the electric-field operator in the cavity-emitter dressed basis, we are able to propose correlation functions that are valid for arbitrary degrees of light-matter interaction. Our results show that the standard photon blo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
402
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(405 citation statements)
references
References 39 publications
3
402
0
Order By: Relevance
“…These results are very promising for the study of light-matter interaction physics, and could lead to applications of coupled organic multiple microcavities in the ultrastrong light-matter coupling regime for the constituent microcavities at room temperature, for example in organic microcavity LEDs, where the coupling effect can narrow the linewidth of emission 23 . The coupled cavity is also an interesting system for realizing photon blockades in the ultrastrong coupling regime 40 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are very promising for the study of light-matter interaction physics, and could lead to applications of coupled organic multiple microcavities in the ultrastrong light-matter coupling regime for the constituent microcavities at room temperature, for example in organic microcavity LEDs, where the coupling effect can narrow the linewidth of emission 23 . The coupled cavity is also an interesting system for realizing photon blockades in the ultrastrong coupling regime 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the solution has a residual oscillation at the driving frequency ω d even in the t → ∞ limit. The steady-state properties are then obtained by averaging the solution over several driving periods, which corresponds to a time integrated measurement in an actual experiment [34]. …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A description of the cavity QED system based on the Rabi model, whose spectrum and eigenstates have been a subject of intensive studies [23,[26][27][28][29][30], is therefore necessary. In order to investigate output photon correlations, which are experimentally relevant for many setups, several works have also considered drivendissipative scenarios [31][32][33][34][35]. They have shown that in the ultrastrong coupling regime, the usual quantum optical master equation and input-output relations led to unphysical predictions and had to be modified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limit is specifically accessible in this frequency range because of the successful implementation of metallic cavities with strongly subwavelength effective volumes [10] which can be combined with quantum heterostructures in semconductors to form hybrid systems [11,12]. In this limit, diverse quantum phenomena have been predicted, such as two-mode squeezing as a consequence of the counter-rotating coupling terms [13], photon blockade [14], conversion from virtual to real photons [15], and decoupling of light and matter for the deep strong coupling regime [16].…”
Section: Introductionmentioning
confidence: 99%